Challenges and Opportunities for Teacher Leaders in Public Schools - Tarraya, Hilger Ojos (Bumi Publikasi Nusantara, 2023)
This study explores the challenges encountered and emerging opportunities for teacher leaders in public schools. It employed the qualitative method of research, specifically phenomenological investigation. There are five participants, determined through purposive sampling. Thematic analysis was utilized in interpreting and analyzing data. Results of the study revealed the following challenges encountered by the teacher leaders: (1) Difficulty in managing time and harmonizing classroom and other functions/ roles; (2) The existence of